Daily sound exposure of hearing aids users during COVID-19 pandemic in Europe - Sun, Kang; Szatmari, Tiberiu-Ioan; Pasta, Alessandro; Bramsløw, Lars; Wendt, Dorothea; Christensen, Jeppe H.; Pontoppidan, Niels H. (Frontiers in Public Health, 2023)
This study aimed to investigate the daily sound exposure of hearing aid (HA) users during the COVID-19 pandemic, with a specific focus on the impact of different governance intervention levels. Modern HA technology was employed to measure and compare the sound exposure of HA users in three distinct periods: pre-pandemic, and two 14-day periods during the pandemic, corresponding to varying levels of governance interventions. The study sample comprised a total of 386 HA users in Europe during the pandemic, with daily sound exposure data collected as part of the main dataset. The results revealed that, during the pandemic, the equivalent continuous sound pressure level (SPL) experienced by HA users decreased, while the signal-to-noise ratio (SNR) increased compared to the pre-pandemic period. Notably, this impact was found to be more pronounced (p<0.05) when individuals were subjected to stronger governance intervention levels, characterized by lower SPL and higher SNR. In conclusion, this study highlights the changes in daily sound exposure experienced by HA users during the COVID-19 pandemic, particularly influenced by the extent of governance interventions that restricted social activities. These findings emphasize the importance of considering the effects of pandemic-related governance measures on the sound environments of HA users and have implications for audiological interventions and support strategies during similar crises.